2018
DOI: 10.1093/mnras/sty2977
|View full text |Cite
|
Sign up to set email alerts
|

Scale dependence of energy transfer in turbulent plasma

Abstract: In the context of space and astrophysical plasma turbulence and particle heating, several vocabularies emerge for estimating turbulent energy dissipation rate, including Kolmogorov-Yaglom third-order law and, in its various forms, j ·E (work done by the electromagnetic field on particles), and − (P · ∇) · u (pressure-strain interaction), to name a couple. It is now understood that these energy transfer channels, to some extent, are correlated with coherent structures. In particular, we find that different ener… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 94 publications
(120 reference statements)
6
58
0
Order By: Relevance
“…Indeed, a key question in plasma physics is whether the end of the MHD range is also the end of the cascade [83][84][85][86][87], or whether there is some energy which continues to be transferred to kinetic scales as suggested in [64,[88][89][90][91][92][93]. Recent studies have shown a possible link between various energy transfer channels, based on proxies for the local energy cascade rate and for energy dissipation [94]. Applying the more rigorous approach presented in this paper to kinetic simulations and Hall-MHD should help understanding what happens for energy transfers at scales where kinetic physics becomes important, especially since the local Hall-MHD term has been derived in [55].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a key question in plasma physics is whether the end of the MHD range is also the end of the cascade [83][84][85][86][87], or whether there is some energy which continues to be transferred to kinetic scales as suggested in [64,[88][89][90][91][92][93]. Recent studies have shown a possible link between various energy transfer channels, based on proxies for the local energy cascade rate and for energy dissipation [94]. Applying the more rigorous approach presented in this paper to kinetic simulations and Hall-MHD should help understanding what happens for energy transfers at scales where kinetic physics becomes important, especially since the local Hall-MHD term has been derived in [55].…”
Section: Discussionmentioning
confidence: 99%
“…More details about the simulation can be found in Ref. 34. We analyze statistics using a snapshot near the time of maximum root mean square electric current density.…”
Section: B Kinetic Plasmamentioning
confidence: 99%
“…However, because of the intrinsic difficulty in estimating the neglected terms from one-dimensional data, this proxy can be used as a first degree approximation in space plasmas time series. The LET was previously used to determine heating regions in the interplanetary plasma [27] and on kinetic numerical simulations [35,37].…”
Section: A a Proxy Of The Local Energy Transfer In Turbulencementioning
confidence: 99%